2007
DOI: 10.1088/1475-7516/2007/07/012
|View full text |Cite
|
Sign up to set email alerts
|

Quark mass uncertainties revive Kim–Shifman–Vainshtein–Zakharov axion dark matter

Abstract: The Kaplan-Manohar ambiguity in light quark masses allows for a larger uncertainty in the ratio of up to down quark masses than naive estimates from the chiral Lagrangian would indicate. We show that it allows for a relaxation of experimental bounds on the QCD axion, specifically KSVZ axions in the 2 − 3 µeV mass range composing 100% of the galactic dark matter halo can evade the experimental limits placed by the ADMX collaboration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…3.2 we have shown that this contribution is negligible compared with the contribution of the peak located at the axion mass. We note that there is a parameter region around F a ∼ 10 6 GeV, called the "hadronic axion window" [56][57][58], that is not excluded by observations. This occurs due to the ambiguity in light quark masses which leads to the cancellation in the axion-photon coupling g aγγ for KSVZ models.…”
Section: 4mentioning
confidence: 99%
“…3.2 we have shown that this contribution is negligible compared with the contribution of the peak located at the axion mass. We note that there is a parameter region around F a ∼ 10 6 GeV, called the "hadronic axion window" [56][57][58], that is not excluded by observations. This occurs due to the ambiguity in light quark masses which leads to the cancellation in the axion-photon coupling g aγγ for KSVZ models.…”
Section: 4mentioning
confidence: 99%
“…In particular, in KSVZ model, it is possible that the axion-photon coupling vanishes due to the uncertainty of the quark mass ratio m u /m d and the bound on g aγγ described above does not significantly constrain the value of F a [58][59][60]. In this case, we have to take the hadronic window into account, but it might be highly model dependent.…”
Section: Cold Axions From the Decay Of Domain Wallsmentioning
confidence: 99%
“…Ref. [9] analyzed the issue in detail also considering the impact of the KM second-order effect in eq. (12).…”
Section: Axion Coupling To Photonsmentioning
confidence: 99%